Does Belief in Supernatural Agents Moderate the Association Between Interpersonal Conflict at Work and Worker Well-Being? - Jung, Jong Hyun (Journal for the scientific study of religion, 2024)
This study examines how interpersonal conflict at work is associated with worker well-being in Singapore. More importantly, it assesses how this association is contingent upon belief in angelic intervention and belief in supernatural evil. Using data from the 2021 Work, Religion, and Health Survey (N = 508), the analyses show that interpersonal conflict at work is positively associated with anxiety and job burnout. In addition, belief in angelic intervention and belief in supernatural evil moderate the association. Specifically, the positive association between interpersonal conflict at work and anxiety is weaker for those who report the belief in angelic intervention. Similarly, higher levels of belief in supernatural evil reduce the positive association of interpersonal conflict at work with anxiety and job burnout. These findings indicate that belief in supernatural agents acts as a key personal resource in the workplace, buffering against the harmful effects of interpersonal conflict at work on worker well-being.